Non-bacterial cystitis caused by pembrolizumab therapy for adenocarcinoma of the lung: a case report - Di, Caixia; Yu, Teng; Ni, Lei (Frontiers in Immunology, 2024)
Immune checkpoint inhibitors (ICIs) including anti-programmed death cell protein 1 (anti-PD1) and anti-programmed cell death-ligand 1 (PD-L1), by disinhibiting the antitumor responses of lymphocytes, have extended survival benefits for patients in lung cancer. ICIs can also lead to a wide spectrum of immune-related adverse events (irAEs), due to dysregulation of immune reactions. Here, we report a 27-year-old female patient with adenocarcinoma of the lung treated with pembrolizumab-combined chemotherapy treatment, who complained of urinary irritation symptoms. No bacteria were found in multiple urine cultures. B-mode ultrasonography indicated a high echo in the right lateral wall of the bladder, about 5.6 × 4.5 mm in size. Transurethral bladder tumor resection (TURBT) was operated. At biopsy, we found CD3+ CD8+ lymphocyte, plasma cell, and eosinophil infiltration and lymphoid follicle formation in the bladder mucosal layer. This is a report of non-bacterial inflammation of the urinary tract caused by immunotherapy.